التعقبات النحوية للإمام ابن جزي على غيره من خلال كتابه التسهيل حروف المعاني - أنموذجا - - زلاسي, مسعود; بوخزنة, حمزة (جامعة الوادي - University of Eloued, 2022)
تُعتبر التعقبات النحوية المتعلقة بحروف المعاني للإمام ابن جزي في ثنايا كتابه الشهير بالتسهيل لعلوم التنزيل، أحد أبرز وأهم المسائل التي تناولها، ونظرا لما لها من أثر في بيان معاني كلام الله وكشف خفاياه وإيضاح غوامضه، اعتنت هذه الدراسة باستقرائها وتتبعها بقصد جمعها ودراستها للوصول إلى خلاصة القول فيها. وسعيا لبلوغ تلك الغاية، وتحقيق ذاك الهدف المنشود، اقتضى هذا الموضوع منا تقسيمه إلى ثلاثة محاور أساسية، تطرقنا في المحور الأول إلى بيان مفهوم التعقب ونشأته وفوائده، بالإضافة إلى معنى حروف المعاني، كما عرّفنا في المحور الثاني بالإمام ابن جزي، بينما اقتصر الكلام في المحور الأخير على دراسة تلك التعقبات التي بلغ عددها بعد تقصينا لها خمس عشرة تعقبا، ترجّح لنا بعد بحثها ومناقشتها في ضوء القواعد وأقوال العلماء أنه أصاب في تسعة منها، وجانب وجه الصواب في الباقي. The grammatical traces related to the letters of meanings mentioned by Imam Ibn Juzay in his famous book, “Al Tashel for the Sciences of Revelation,” is one of the most prominent and most important issues that he addressed, and due to its impact on clarifying the meanings of God’s words and revealing its hidden and ambiguities. To sum it up. In order to achieve that end, and to achieve that desired goal, this topic required us to divide it into three main axes. In the first axis, we touched on the explanation of the concept of tracing, its origins and benefits, in addition to the meaning of the letters of meanings, as we defined in the second axis by Imam Ibn Juzy, while the speech was limited to The last axis on the study of those traces, whose number reached fifteen after our investigation, after researching and discussing them in the light of the rules and the sayings of scholars, that he was correct in nine of them, and the right side in the rest.
مقال
Keywords: التعقبات ; النحو ; حروف المعاني ; ابن جزي ; التسهيل